Care for the Visa: Maximising Mobility from Northwest Russia to the Schengen Area - Tkach, Olga (Nordic Journal of Migration Research, 2023)
This article analyses how and why the residents of Northwest Russia—holders and users of the unified Schengen multiple-entry ‘C’ visas issued by the state of Finland—care for their visas by balancing trips to Finland against trips to the wider Schengen Area, according to the rules that require such balancing. Applying the concept of productive work and reproductive labour, and drawing on in-depth interviews with the Schengen visa-dependants in Russia, I show how Schengen visa policies operate on the local level of the EU’s external border. The article explores how such visas facilitate short-term mobility, yet require from their holders constant efforts to maintain this resource, and therefore operate as a nexus of freedom of movement and commitment. I argue that the role of the short-term Schengen visa issued to non-EU visitors goes far beyond simple permission for crossing the border and materialises as a facilitator of Europe-wide mobility and, therefore, an object of constant care. Peer reviewed